Peran Pemerintah Terhadap Motivasi dan Inovasi Masyarakat dalam Meningkatkan Kinerja Desa Mandiri di Karang Agung Kec. Tanjung Palas Utara Kab. Bulungan - Suhardyman, Suhardyman; Syahran, Syahran; Juhana , Juhana (Syntax Corporation, 2026)
This study examines the role of government on community motivation and innovation in improving the performance of Karang Agung Independent Village, North Tanjung Palas District, Bulungan Regency. The phenomenon of independent villages remains rare in North Kalimantan with only 11 out of 447 villages achieving this status. The research employs a quantitative approach using Structural Equation Modeling (SEM) based on PLS-SEM with SmartPLS 4 software. Data were collected through questionnaires from 269 respondents who are heads of households in Karang Agung Village with criteria of minimum age 17 years, minimum senior high school education, and permanent residence for at least two years. The results indicate that government role has a positive and significant effect on community motivation, community innovation, and independent village performance. The government's role as stabilizer, innovator, modernizer, pioneer, and development implementer proved to increase community motivation in actively participating in village development. Community motivation and innovation also proved to have positive and significant effects on improving independent village performance reflected through job creation, economic activities based on local wisdom, development independence, and reduced rural-urban development disparities. This research provides theoretical contributions to the development of human resource management concepts at the village level and practically can serve as a reference for other villages in their efforts to achieve independent village status through strengthening government role, increasing motivation, and developing community innovation.